Benefit of implantable cardioverter-defibrillator therapy after generator replacement in patients with Brugada syndrome. (6th May 2015) - Kim, Ju Youn; Kim, Sung-Hwan; Kim, Sung Su; Lee, Ki Hong; Park, Hyung-Wook; Cho, Jeong-Gwan; Uhm, Jae-Sun; Joung, Boyoung; Pak, Hui-Nam; Lee, Moon-Hyoung; Park, Seung-Jung; On, Young Keun; et al.
Abstract: Background: An implantable cardioverter-defibrillator (ICD) is the only proven effective therapeutic strategy for patients with Brugada syndrome (BS). However, it is controversial whether the device should be replaced even in patients who had never experienced appropriate ICD therapy until the time of generator replacement. Methods and results: This was a nationwide, multicenter retrospective study that enrolled patients who were diagnosed with BS and had an ICD implantation between January 1998 and April 2014. Appropriate ICD therapies administered for ventricular tachyarrhythmia were evaluated during follow-up. A total of 117 patients (age 43 ± 12 years, male 115 [98.3%]) were enrolled, and the mean follow-up duration was 6.0 ± 4.1 years. Thirty-seven (31.6%) patients had experienced appropriate ICD therapy during follow-up. Of all patients, 46 underwent replacement of the device. After the first generator replacement, the incidence of appropriate ICD therapy remained as high as 65.2% in patients who previously experienced appropriate ICD therapy before generator replacement. In 30 patients who did not experience any cardiac events until the first generator change, two (8.7%) had an episode of appropriate ICD therapy afterwards. Conclusions: No episode of ICD therapy before generator replacement could not guarantee a safe clinical course. ICD generator replacement should be considered even in patients without ICD therapy before.